2016
DOI: 10.1080/21655979.2016.1169355
|View full text |Cite
|
Sign up to set email alerts
|

The role ofbudABC on 1,3-propanediol and 2,3-butanediol production from glycerol inKlebsiella pneumoniaeCICIM B0057

Abstract: ABSTRACT1,3-propanediol (1,3-PD) is an important compound from which many others can be synthesized. 2,3-butanediol (BDO) is the key by-product in the biosynthesis of 1,3-PD from glycerol, but it impedes its downstream purification. In Klebsiella, the budA, budB and budC genes encode enzymes that are responsible for the synthesis of BDO. In this study, 3 individual antisense RNAs were designed to repress the expression and hence activity of BudA-C. Compared with the parent strains, the activities of BudB and B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 24 publications
(24 reference statements)
0
3
0
Order By: Relevance
“…[61][62][63] The 1,3-PDO synthesis from glucose can proceed via two steps with natural organisms or via one step, if the organisms are genetically engineered for that purpose. [64,65] It has been shown that monomers synthesised via this method contain less impurities than the 1,3-PDO produced from petroleum-based reagents. [57] Figure 6.…”
Section: Hc Chmentioning
confidence: 99%
“…[61][62][63] The 1,3-PDO synthesis from glucose can proceed via two steps with natural organisms or via one step, if the organisms are genetically engineered for that purpose. [64,65] It has been shown that monomers synthesised via this method contain less impurities than the 1,3-PDO produced from petroleum-based reagents. [57] Figure 6.…”
Section: Hc Chmentioning
confidence: 99%
“…As regards the indirect means of plant growth promotion, in P. agglomerans C1 genome, we found (Table 4) genes encoding enzymes involved in the synthesis of volatile organic compounds (acetoin and 2,3-butanediol; [43,44], Gamma-Aminobutyric Acid (GABA) [45], and siderophores [46], as well as genes encoding the three components of EfeUOB transporter, a ferrous iron transporter induced by low pH and low iron [47].…”
Section: Plant Beneficial Properties Of Pantoea Agglomerans C1mentioning
confidence: 99%
“…Similar negative results were obtained when disrupting the acetate synthesis pathway by deactivating the ackA-pta gene (data not shown). This might due to the fact that both metabolic pathways play an important role in cell growth by balancing the intracellular acetyl-CoA pool, energy supply, and synthesis of branched-chain amino acids (Lu et al, 2016;Ohtake et al, 2017). Therefore, the 2,3-butanediol and acetate synthesis pathways were remained complete and the strain Kpr-2 was constructed by further deleting the fumarate reductase gene (frdA, GenBank accession no.…”
Section: Rewiring Glycerol Metabolism For Efficient 13-pd Productionmentioning
confidence: 99%